The Implementation of Public Information Disclosure and Transparency by Public Bodies in Bengkulu Province (A Study of the Bengkulu Province Information Commission): Implementasi Keterbukaan Dan Transparansi Badan Publik Di Provinsi Bengkulu (Studi Komisi Informasi Provinsi Bengkulu ) - Endo Pratama Putra; Henny Aprianty; Bobby Mandala Putra (Gayaku Publisher, 2026)
Public information disclosure is an important principle of good governance as mandated by Law Number 14 of 2008 on Public Information Disclosure. This study aims to analyze the implementation of openness and transparency of public bodies in Bengkulu Province through a case study of the Bengkulu Provincial Information Commission. A qualitative descriptive method was employed using interviews, observation, and documentation. Data were analyzed using the Miles and Huberman model and George Edward III’s implementation theory. The findings show that public information disclosure has been implemented through monitoring and evaluation, information dispute resolution, public outreach, and PPID supervision. However, challenges remain, including limited human resources, budget constraints, inadequate facilities, and low understanding of information disclosure among some public bodies. Efforts to address these issues include strengthening PPID capacity, improving coordination, and optimizing information technology in public services.